GENDERED SPACE IN WEST SUMBA TRADITIONAL HOUSES - NURDIAH, Esti Asih; ASRI, Altrerosje; HARIYANTO, Agus Dwi (DIMENSI (Journal of Architecture and Built Environment), 2016)
Rendell stated that gender representation underlined the production of space in architecture both symbolically and functionally in certain cultures (Rendell et al. 2000). Thus, an exploration on the spatial functionality of traditional houses could show how cultural gender rules and roles generate the spatial arrangements. This empirical research explored the traditional houses in two kampongs: Tarung and Ratenggaro of West Sumba, Indonesia, which spaces are divided into two distinct spaces: male’s space and female’s space, each with its own entrance. This firm division leads to the questions on its relation with the traditional gender roles are represented inside the house. Interestingly, the spatial arrangement is not intended to create separation between men and women inside the house or to pose that the status and roles of men are higher than those of women. The research found that the space separation actually is a manifestation of the dynamic roles of male and female members of the house and the circular arrangement of the space around the fireplace at the centre of the house follows the dynamic of gender duality in Sumba culture.